KEPEMIMPINAN KETUA YAYASAN BERDASARKAN KECERDASAN EMOSIONAL (EQ) DI SMK TEKNIK KIMIA PALEMBANG TAHUN PELAJARAN 2022/2023 - Aryani, Nisa; Setyaningsih, Rina; Supadi, Ari (UNISAN JURNAL, 2024)
The success of education in an educational institution that shelter the Foundation is determined by berabagi kinds of factors, one of which is Leadership Chairman of the Foundation. There are several points of view in viewing a person's leadership berdasrakan intelligence owned. Emotional intelligence is one point of view that is able to analyze the leadership of a chairman of the foundation. Educational Institutions Foundation SMK Teknik Kimia Palembangt is one of the developing foundations in Sukamarga Regency. Leadership of Foundation chairman based on emotional intelligence (EQ) is considered very good. This has a positive impact on the sustainability of the organization's foundation. Therefore the researchers tried to analyze the leadership of the chairman of the Institute of Education Institutions SMK Teknik Kimia Palembang focused from the point of view of his emotional intelligence.This research is a qualitative research that describes the leadership of the Chairman of the Institute of Education Institutions SMK Teknik Kimia Palembang and analyze the point of view of emotional intelligence. This research was conducted with observation, interview and documentation techniques. Testing the validity of the data using triangulation techniques, which in this study is more emphasized to triangulation techniques sources. The source is all citizens of the good foundation of board, environment, people around including teachers in elementary, junior high and vocational school SMK Teknik Kimia Palembangt Syafa'at Sukamarga. The source will contain the leadership data of the chairman of the SMK Teknik Kimia Palembang Foundation based on emotional intelligence.The results showed that, chairman of the foundation SMK Teknik Kimia Palembang have good leadership regarded from the angle of emotional intelligence. The results of the analysis show that the chairman of the foundation runs a primal leadership leadership very well. It is proven by triangulation of data and source. Chairman of the SMK Teknik Kimia Palembangt Institute of Educational Institutions Intercession Tulang Bawang has a high commitment to the future vision, especially during times of stress or in the midst of increasing responsibility. The chairman of the foundation takes an emotional approach to all citizens within the foundation. The Chairman of the Foundation is able to read his own emotions and recognize their impact using instinct to guide decisions, know their strengths and limitations, be able to control emotions and show honesty and integrity, trustworthiness. Chairman of the Foundation has self-awareness and good self- management, good social awareness and good relations management.